The Propaganda Power of Urban Views in Selim III's Ottoman Empire - Uğurlu, A. Hilal (Pera Museum Publication 115, 2023)
Istanbul, the capital of the Ottoman Empire since the mid-fifteenth century, boasts a rich history of panoramic representations that have captivated artists and patrons alike. From the early years, artists affiliated with the retinue of ambassadors to the Ottoman Empire played a significant role in creating these expansive city views. Melchior Lorck’s 11.27-meters long panoramic view of Istanbul, drawn between 1559 and ca. 1563, is one of the earliest attempts to portray the city accurately and in panoramic format. Lorck was an artist assigned to the entourage of the German ambassador to Istanbul, Ogier Ghiselin du Busbecq. In the eighteenth century, the changing nature of diplomatic relations between the Ottoman Empire and European polities led to an increase in the number of embassies and, consequently, the number of artists appointed to these posts. This increase in artistic activity was reflected in the growing number of city views and topographical landscapes of Istanbul produced during this period. Concurrently, the emergence of philhellenism in Europe, coupled with the proliferation of picturesque travel literature, augmented the attention to the Ottoman lands and its capital.
Keywords: Egyptology; Ottoman History; Nineteenth Century Studies; Panoramas; Painting; Political Legitimacy; Egypt; History of Ottoman Art and Architecture; Late Ottoman History; Eighteenth Century Print Culture; Istanbul; Antiquarianism in the Eighteenth century; Visual Representation